2011
DOI: 10.1021/np200329a
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented Ultra-High-Resolution Hydroxy Group 1H NMR Spectroscopic Analysis of Plant Extracts

Abstract: A general method is demonstrated for obtaining ultra-high resolution in the phenolic hydroxy group 1H NMR spectroscopic region, in DMSO-d6 solution, with the addition of picric acid. Line-width reduction by a factor of over 100 was observed, which resulted in line-widths ranging from 1.6 to 0.6 Hz. This unprecedented resolution, in combination with the shielding sensitivity of the hydroxy group absorptions to substituent effects at least up to 11 bonds distant and the application of 2D 1H-13C HMBC techniques, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
17

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 19 publications
(37 reference statements)
0
47
0
17
Order By: Relevance
“…Hence, the parameters which allowed a valuable qualitative analysis were maintained .The integrals of 1 H NMR spectra were used for quantitative determinations because the integrals give the relative measure of the number of resonating nuclei. Accurate integrations can be obtained if the relaxation delay is 5 times longer than the T 1 [18][19]. Modern instruments allow for extremely accurate integration of the peak area.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the parameters which allowed a valuable qualitative analysis were maintained .The integrals of 1 H NMR spectra were used for quantitative determinations because the integrals give the relative measure of the number of resonating nuclei. Accurate integrations can be obtained if the relaxation delay is 5 times longer than the T 1 [18][19]. Modern instruments allow for extremely accurate integration of the peak area.…”
Section: Resultsmentioning
confidence: 99%
“…The denoted peaks 5-7 displayed the typical of flavonoids UV spectra, (UV maxima at 260-270 nm and 340-350 nm) (De Rijke et al, 2006); the 1 H NMR spectra of these peaks in aprotic organic solvent indicated a significantly deshielded signal in the region of 11-13 ppm, which is of high diagnostic value. Previous NMR studies of crude plant extracts revealed that these peaks could be attributed to the C-5 OH of flavonoids that participate in a strong intramolecular hydrogen bond with the oxygen atom of C-4 carbonyl group resulting in relatively sharp resonance (Charisiadis, Primikyri, Exarchou, Tzakos, & Gerothanassis, 2011;Exarchou, Godejohann, van Beek, Gerothanassis, & Vervoort, 2003;Exarchou, Troganis, Gerothanassis, Tsimidou, & Boskou, 2002). The peaks 5-7 were also identified easily from their distinctive spin-spin coupling in the aromatic region of 1 H NMR spectrum.…”
Section: Phytochemical Composition Of Mountain Tea Decoctionmentioning
confidence: 99%
“…NMR experiments were used for the quantitative analysis of the extracts, the procedure followed is described in ref. 10 In vitro glycation of BSA BSA (10 mg/mL, fatty acid-free) was modified in vitro at 37°C by the reducing sugars, ribose or fructose (500 mM). All incubations were carried out in 0.1 M phosphate buffer (pH 7.4) in the absence and presence of different concentration of extracts (1-100 lg/mL), pure compounds (1-100 lM), and AG (1 mM).…”
Section: Nmr Experimentsmentioning
confidence: 99%
“…Using NMR spectroscopy the concentration levels (mg/g) of the constituents of the two extracts were calculated with the method of spiking with the standard compounds at known concentration. 10,15 The quantitative results are summarized in Table 2. The quantitative results provided by NMR data are in good agreement with those obtained by HPLC.…”
Section: Fig 1 Total Ion Chromatogram Of Methanol Olive Leaf Extracmentioning
confidence: 99%